Global Burden of Atrial Fibrillation and Flutter by National Income: Results From the Global Burden of Disease 2019 Database - Ohlrogge, Amelie H.; Brederecke, Jan; Schnabel, Renate B. (Journal of the American Heart Association, 2023)
Background Atrial fibrillation (AF) and atrial flutter (AFL) are common conditions that can lead to significant morbidity and death. We aimed to understand the distribution and disparities of the global burden of AF/AFL as well as the underlying risk factors. Methods and Results Data on the AF/AFL burden from the Global Burden of Disease data set were analyzed for the years 1990 to 2019, with countries grouped into low, lower-middle, upper-middle, and high national income classes according to World Bank categories. Data were supplemented with World Health Organization and World Bank information. The prevalence of AF/AFL has more than doubled (+120.7%) since 1990 in all income groups, though with a larger increment in middle-income countries (+146.6% in lower-middle- and +145.2% in upper-middle-income countries). In absolute numbers, 63.4% of AF/AFL cases originate from upper-middle-income countries, although the relative prevalence is highest in high-income countries. Prevalence of AF/AFL appears to be correlated with medical doctor rate and life expectancy. The most relevant AF/AFL risk factors are unevenly distributed among income classes, with elevated blood pressure as the only risk factor that becomes less common with increasing income. The development of these risk factors differed over time. Conclusions The global burden of AF/AFL is increasing in all income groups and is more pronounced in middle-income countries, with further growth to be expected. Underdiagnosis of AF/AFL in low- and middle-income countries may contribute to lower reported prevalence. The risk factor distribution varies between income groups.